2008
DOI: 10.1007/s11998-008-9127-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nano-Al2O3 particles on the corrosion behavior of alkyd based waterborne coatings

Abstract: A modification in the alkyd based waterborne coatings was studied with the addition of 0.05%, 0.1%, 0.2%, and 0.3% nano-Al 2 O 3 . Corrosion performance of the nano-composite coatings were evaluated by applying these nanocomposites on mild steel substrate and exposing them to salt spray, humidity, and accelerated weathering. Mechanical properties were studied by subjecting the coating to scratch and abrasion test. The results showed that, with an increase in the concentration of nano-Al 2 O 3 there was an impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 8 publications
2
39
0
Order By: Relevance
“…The importance of nanoparticles compared to conventional micro sized fillers is mainly due to their small size and large specific surface area. The decrease in size of the particles causes mechanical properties enhancement of the coating [11][12][13]. Therefore, various nanoparticles have been employed as reinforcements to improve coatings performance under the corrosive environments, including TiO 2 [14], ZnO [15], CaCO 3 [16], Fe 2 O 3 [17], SiO 2 [18], and etc.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of nanoparticles compared to conventional micro sized fillers is mainly due to their small size and large specific surface area. The decrease in size of the particles causes mechanical properties enhancement of the coating [11][12][13]. Therefore, various nanoparticles have been employed as reinforcements to improve coatings performance under the corrosive environments, including TiO 2 [14], ZnO [15], CaCO 3 [16], Fe 2 O 3 [17], SiO 2 [18], and etc.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of different nano-sized pigments on the properties of alkyd-based NCs was extensively investigated in the literature [26][27][28][29][30][31][32][33][34][35][36][37]. It has been shown that application of zinc oxide (ZnO) as nanosized pigment improves mechanical and thermal properties [26] and corrosion resistance [27] of alkydbased coatings.…”
mentioning
confidence: 99%
“…The presence of nanoferrite (Fe 3 O 4 ) in soy alkyd coating improved thermal stability, physico-mechanical properties and corrosion resistance [34]. The addition of aluminum oxide (Al 2 O 3 ) nano-sized pigment into the alkyd coatings improved its corrosion [35,36] and UV resistance and mechanical properties, without altering the optical clarity of the prepared coating [36]. Alkyd paint prepared using molybdenum oxide (MoO 3 ) NPs showed good antibacterial properties against pathogenic bacteria [37].…”
mentioning
confidence: 99%
“…ZnO nanoparticle) possesses unique characteristics such as improved chemical, biological, semi-conductor properties and drug delivery. Nano-sized ZnO particles have also been found to be inert, non-toxic in nature and possess a blanket for UV radiation (due to its wide band gap of 3.37 eV, large bond strength and its heavy 60 meV excitation binding energy at room temperature) [15][16][17][18] . The inorganic amphoteric oxide (i.e.…”
Section: Microbes Such As Escherichia Streptococci Andmentioning
confidence: 99%